Multilayer TiB2/X hard coatings by sputtering deposition - Da Silva, Maria de Fatima Oliveira Vales (Cranfield University, 1998)
Titanium diboride has been investigated as a potential candidate for aerospace structures, cutting tools, surface coatings of first-wall components and diffusion barriers in integrated circuit metallization. Titanium diboride is a very stable hard refractory compound but its brittleness is the main drawback. It was possible to lessen the TiB2 brittleness by producing TiB2/X coating designs by the multi-target RF magnetron sputtering process. X is the metal layer (Al, Ti, NiCr, Mo) in the composite system. The influence of the composition wavelength and volume fraction of ceramic has been studied over a range of sputtering conditions. The most suitable multilayer coating design (TiB2/NiCr) on steel substrate, for maximum hardness (18.81GPa) and elastic modulus (304.6GPa) was found to be with a composition wavelength of 50nm and volume fraction of ceramic of 75%. The greatest improvement of the elastic modulus measured by nanoindentation was found to be for a TiB2/Al two-layer coating design either on steel or on aluminium substrate, giving 36.2% and 40% improvement above the rule of mixtures respectively, when compared with TiB2 coatings deposited under the same sputtering conditions. Several pieces of three-point bent apparatus were designed for measuring the inplane elastic modulus of the coatings. The three-point bent test by nanoindenter shows promise as a method for measuring the in-plane elastic modulus on uncoated beams. A comparison between traditional and non-traditional methods of measuring mechanical properties of the coatings was performed in this study. The nanoindentation technique was found to be an appropriate method to measure the mechanical properties of multilayer coating designs.